A comparative corpus-based ecological discourse analysis of Chinese, Indian, and American news reports on the Belt and Road Initiative (2013–2022) - Wei Ruby Rong; Hu Yanlan (Journal of World Languages)
This study employs corpus-based ecological discourse analysis to explore representations of the ecological attitudes in English-language news reports on China’s Belt and Road Initiative (BRI) in China, India, and the United States from 2013 to 2022. It reveals the media’s perception and attitude towards the BRI in these nations. The analysis reveals that media outlets in each country project different ecological stances using varied attitudinal resources. The Chinese media frequently deploy beneficial attitudinal resources to highlight the BRI’s achievements and advocate for broader international engagement. In contrast, the Indian media exhibit a balanced usage of beneficial, neutral, and destructive attitudinal resources, reflecting a prudent and observant attitude towards the BRI. The American media corpus displays a greater prevalence of neutral and destructive attitudinal representations over beneficial ones, suggesting a comparatively skeptical reception of the initiative. The study argues that these divergent patterns of ecological attitudes and the selection of attitudinal resources are shaped by factors such as economic development, geographical context, and social values.